PENGARUH AIR BERSIH DAN STATUS EKONOMI TERHADAP KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS TAPUNG HILIR II - Riski Novera Yenita; Masyitha Ramadhani; Evy Saputri (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
Infant and toddler mortality rates due to diseases that can be prevented by immunization still show quite high rates. Basic immunization serves to protect and reduce the risk of morbidity and mortality from diseases that can be prevented by immunization. The purpose of this study was to determine the factors that influence mothers in providing routine routine immunizations in the work area of ​​Inuman Health Center. This type of research is observational analytic with the